Development of Interactive Google Sites-Based Learning Media to Improve Senior High School Students’ Understanding of Stoichiometry - Mutiara Agustina Nst.; Rabiah Afifah Daulay; Dwy Puspita Sari; Mutia Ardila (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Chemistry is one of the fields of science with abstract concepts and unique vocabulary. That is why chemistry is considered as one of the subject matter that is considered difficult. Stoichiometry is one of the chemistry materials that is considered difficult due to its abstractness. This study aimed to develop and validate an interactive web-based learning media using Google Sites to enhance students’ understanding of stoichiometry. The research employed a Research and Development (R&D) method, including needs analysis, design, development, and validation stages. Data were collected in qualitative and quantitative forms, with quantitative data obtained through validation questionnaires using a 5-point Likert scale. The validation involved two expert validators, consisting of media and material experts. The results showed a validity score of 89% from media experts and 90% from material experts, with an overall average of 90%, categorized as highly feasible. The developed media includes interactive features such as virtual laboratories, learning videos, and 20 online quiz questions. These findings indicate that the Google Sites-based learning media is valid and suitable for supporting chemistry learning, particularly in improving students’ engagement and understanding of stoichiometry.